(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Many ongoing scientific studies have focused on the development of nephrogenesis, tubular function, and vascular development in premature infants, which can help to identify the mechanisms of development of such diseases and prevent their occurrence.